Analisis Faktor Internal terhadap ROA dengan CAR sebagai Intervening pada Perbankan yang Tedaftar di BEI Tahun 2018- 2020 - Nur Fadhilah; Sri Hermuningsih ; Gendro Wiyono (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose based on this research is to analyze the internal factors of NPL (Non-Performing Loan), LDR (Loan to Deposit Ratio) to ROA (Return on Assets) using CAR (Capital Adequacy Ratio) in intervening and in this research sample using the banking sector contained in the Stock Exchange. The Indonesian Stock Exchange (IDX) from 2018 to 2020 uses 45 banks. By using purposive sampling technique, based on this research, there are still 32 companies. The quantitative data method is attached to the financial statements for that year. In this research sample, the banking sector on the Indonesia Stock Exchange (IDX) from 2018 to 2020 uses 45 banks. By using purposive sampling technique, based on this research, there are still 32 companies. The quantitative data method is attached to the financial statements for that year. So that this research results: (1) LDR has no effect on CAR, (2) NPL has no effect on CAR. (3) LDR has no effect on ROA, (4) NPL has a positive and significant effect on ROA, (5) CAR has no effect on ROA. Keywords: NPL (Non Performing Loan), LDR (Loan to Deposit Ratio), ROA (Return on Assets)